Music production : recording : a guide for producers, engineers and musicians - Ferreira, Carlos Lellis (Focal Press, 2013)
Your recording can make or break a record, and a clean recording is an essential catalyst for a record deal. Professional engineers with exceptional skills can earn vast amounts of money be in demand from the biggest acts. To develop such skills you need to master both the art and science of recording. Rehearsal to Monitor Mix gives you all you need to know, the tools and techniques, to put into practice and improve your recording. Covering the entire process from fundamental concepts to advanced techniques and offering a multitude of tips and tricks and audio samples, this book has it all. Carlos Lellis teaches you, how to craft and evaluate your recording then take it a step further. He describes the theory and the tools used how these are put into practice and then shows you how they are put together. Using audio and visual materials and field observations to aid with explanations Packed full of photos, graphs, diagrams and audio samples, Rehearsal to Monitor Mix is a vital read for anyone wanting to succeed in the field of recording.